Desing jako narzędzie innowacji - Wicher-Baluta, Agnieszka (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
Innovations make it possible to accelerate economic growth and overtaking in global competition, they are a cornerstone in building a competitive advantage. We can say that innovative solutions to decide nowadays about the visibility and success of your business. The main thesis concerning the article says that the design is a tool of innovation. Under this role, design can be a primary determinant of innovative strategy development, it may be at the center of a comprehensive vision of the objectives, asses available resources and possibilities for their use or can be the basis of specific methods and sequence of actions to achieve progress and solve key problems of the company. Against this background, a crucial questions arises, how to generate innovative solutions based on design? The purpose of this paper is to present two innovative methodologies in the area of design management: radical innovation and co-creation and present their implications for innovations.